Cytogenotoxic potential of Malva parviflora L. cultivated under different light conditions - Cássia Becker Böck; Carmine Aparecida Lenz Hister; Solange Bosio Tedesco (Acta Scientiarum: Biological Sciences, 2023)
For many centuries, the treatment with medicinal plants was the only means accessible to various ethnic groups, and nowadays plants are still widely used in the treatment of diseases, besides being the raw material for several drugs. However, many of these plants may present unknown genotoxic effects, making their consumption a health risk. Species such as Malva parviflora L. have been used by the general population for medicinal purposes: antifungal, anti-inflammatory, analgesic, and antioxidant. This study had the objective of analyzing the cytogenotoxic potential of aqueous extracts of this Malva species using the Allium cepa test, which serves as a bioindicator of the genotoxicity of plant extracts. Forty-four seedlings of M. parviflora were grown for 36 days between November and December 2020, in a greenhouse in two groups: half of the plants were protected with a shading screen, and the rest were not. The aqueous extracts were prepared from the aerial part and roots (fresh and dehydrated), at the concentration of 5 g L-¹. The bulbs of A. cepa were left for 24 hours in the treatments, plus the negative (distilled water) and positive (glyphosate 1.5%) treatments. The roots of the bulbs were collected, placed in the fixative for 24 hours, transferred to 70% alcohol, and stored in a refrigerator. The slides were prepared by the crushing technique, and cells in the division and with chromosome alteration were analyzed, mitotic and genotoxic index were calculated, and statistical analysis was done by the Chi-square and Scott-Knott tests. From the results obtained, it is possible to conclude that the aqueous extracts of M. parviflora at a concentration of 5 g L-¹ present antiproliferative activity, but are not genotoxic. The cultivation mode is relevant, that is, with and without shading the fresh leaves present a difference in cell proliferation, but the same does not occur with the dried leaves.